Atomistic underpinnings for growth direction and pattern formation of hcp magnesium alloy dendrite. (December 2018) - Du, Jinglian; Zhang, Ang; Guo, Zhipeng; Yang, Manhong; Li, Mei; Liu, Feng; Xiong, Shoumei
Abstract: The three-dimensional (3D) growth pattern, preferred growth directions and the underlying growth mechanism of magnesium alloy dendrite are investigated via 3D experimental characterization and multiscale mathematical simulations. It is found that the formation of the dendritic microstructure is associated with the magnitude of surface energy anisotropy. The results based on synchrotron X-ray tomography and electroback scattered diffraction techniques show that typical 3D morphology of the α-Mg dendrite exhibits an 18-primary-branch pattern, with six along the < 11 2 ¯ 0 > basal direction, and the other twelve along the < 11 2 ¯ 3 > nonbasal direction. The underlying mechanism is investigated by performing relevant atomistic calculations at the ground state and the elevated temperatures in light of density functional theory (DFT) and quasi-harmonic approximation (QHA). The results indicate that the preferred growth direction for the α-Mg dendrite growth is < 11 2 ¯ x > rather than < 10 1 ¯ x >, and the anisotropic surface energy decreases as the temperature increases. Subsequent analysis further confirms that the preferred growth directions of the α-Mg dendrite at different temperatures correspond consistently to those orientations with higher surface energy anisotropy, i.e., the < 11 2 ¯ 0 > and < 11 2 ¯ 3 > . Accordingly, the 3D phase-field simulations are performed to investigate the growth behavior of the α-Mg dendrite, with the anisotropic strength determining via DFT-based calculations. Graphical abstract: Image 1